Optimal Magnetizing Inductance Design Method for a Two-Switch Forward Converter - Sanghyuk Ji; Eurak Jung; Yohan Jang; Sungwoo Bae (IEEE Access)
This paper proposes an optimal design method for the transformer magnetizing inductance of a Two-Switch Forward Converter (TSFC) to achieve its maximum efficiency. The selection of a magnetizing inductance significantly affects the associated major losses, making it challenging for designers to choose the appropriate value. It is crucial to design the magnetizing inductance that minimizes the total losses by mathematically analyzing the losses related to the TSFC elements. This paper analytically investigates the impact of the transformer magnetizing inductance on the losses of TSFC components. A simple mathematical loss modeling approach is used to propose a method for selecting the optimal magnetizing inductance. To verify the proposed optimal magnetizing inductance selection method, a 500 W TSFC prototype was designed. The prototype was used to experimentally compare transformers with different magnetizing inductances, validating the effectiveness of the proposed method. The experimental results demonstrate that the proposed method can achieve the maximum efficiency of TSFC by selecting the optimal magnetizing inductance.